DETERMINATION OF ANTIBIOSIS OF Trichoderma species AGAINST FUNGI ASSOCIATED WITH CORN (Zea Mays L.) SPOILAGE (FUDMA JOURNAL OF SCIENCES, 2024)
Biological control of food spoilage microorganisms is gaining more attention because it is a safe and cheap technique. This study evaluated the antagonistic potential of Trichoderma species against corn spoilage fungi by plate co-culture technique for seven days. Fungal isolates from corn spoilage were examined morphologically and microscopically. The percentage growth inhibition (PGI) of Trichoderma species against the corn spoilage fungi were A. flavus (15%), A. niger (14%), A. terreus (62.9%), Fusarium spp. (5.9%), Nigrospora spp. (61.4%) and Penicillium spp. (62.5%). The result obtained in this study revealed that Trichoderma spp. had significant inhibitory effects against the growth of fungal pathogens associated with corn spoilage. Therefore, it could be explored for control of post-harvest fungal spoilage of corn. It is recommended that in order to compare the antagonistic strength of the Trichoderma species, different species of Trichoderma should be tested against the same spoilage fungi.
Keywords: Biological control; Trichoderma Species; Corn Spoilage; Antagonistic; Penicillium spp.